Genetic studies of accelerometer-based sleep measures yield new insights into human sleep behaviour - Samuel E. Jones (Nature Portfolio, 2019)
Quality, quantity and timing of sleep are important factors for overall human health. Here, the authors perform GWAS for sleep traits estimated using wearable accelerometers and identify 47 genetic associations, including 26 novel associations for measures of sleep quality and 10 for nocturnal sleep duration.